ANXIETY (KECEMASAN) DAN CARA MENGATASINYA MENURUT SAYYID QUTHB DALAM TAFSIR FĪ ẒILĀL AL- QUR’ĀN - wulan rahmawati; Muchlis Daroini (At-Tafasir Journal of Quranic Studies and Contextual Tafsir, 2025)
Anxiety is an emotional condition characterized by feelings of discomfort, fear, and worry about uncertain future events. This study uses a qualitative literature review method, focusing on an in-depth understanding of written sources, especially Sayyid Qutb's Tafsir Fī Ẓilāl Al-Qur'ān which is supported by books, journals, and articles. The data were analyzed descriptively and systematically by presenting Sayyid Qutb's interpretation. This study interprets Sayyid Qutb's views on the symptoms, factors causing anxiety, and how to overcome it. Anxiety is seen as a mental state that arises due to fear of the future, and weak faith. He advocates a spiritual approach to overcoming anxiety through dhikr, tawakal, and patience, which aims to achieve inner peace. Sayyid Qutb's interpretation has advantages and disadvantages. The advantages are in terms of simple language style, and easy to understand. However, this interpretation has disadvantages, especially in terms of the lack of in-depth explanation of the meaning of the words in the verse and Sayyid Qutb's limitations in compiling his work